Research of CdS/L-cystein colloid solutions using the method of mathematical planning - Krupko, Olena (Physics and Chemistry of Solid State, 2024)
In the work, the additive effect of the content of crystal-forming ions Сd2+ and S2- and the stabilizer L-Cys using the method of mathematical planning of the experiment on the process of formation of CdS/L-Cys nanoparticles in potentially oxidizing conditions (without deaeration of precursor solutions) and the optical properties of colloidal solutions were investigated. obtained under conditions of pH = 7 and temperature of 220C. By statistical processing of the results, equations were obtained and diagrams of concentration dependences of the wavelength of the optical absorption edge of colloidal solutions of CdS semiconductor nanoparticles in the Сd2+ – L-Cys – S2- system were constructed.